2022
DOI: 10.1177/00472875211066112
|View full text |Cite
|
Sign up to set email alerts
|

Planning Horizon in International Travel Decision-Making: The Role of Individual and Cultural Determinants

Abstract: A solid understanding of when travel decisions are made in relation to travelers’ planning horizons is crucial for travel service providers. Despite its importance, there are very few empirical studies investigating the planning horizon and its antecedents in travel research literature. This study contributes to bridging this gap by conceptualizing a two-level model of antecedents of travelers’ planning horizons. In addition to individual traveler- and trip-related aspects, the model provides a cross-cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 81 publications
2
13
0
Order By: Relevance
“…Similarly, they reported fewer days in trip planning for high UA respondents. Elsewhere, studies did not find significant evidence of the role of UA on planning time/ horizon: Crotts (2004) did not find significant differences between US nationals travelling to high or low UA country, while Backhaus et al (2022) found that UA only had a marginal effect on travel planning travel to European countries.…”
Section: Trip-planning Behaviour Under Ordinary Circumstancesmentioning
confidence: 98%
See 4 more Smart Citations
“…Similarly, they reported fewer days in trip planning for high UA respondents. Elsewhere, studies did not find significant evidence of the role of UA on planning time/ horizon: Crotts (2004) did not find significant differences between US nationals travelling to high or low UA country, while Backhaus et al (2022) found that UA only had a marginal effect on travel planning travel to European countries.…”
Section: Trip-planning Behaviour Under Ordinary Circumstancesmentioning
confidence: 98%
“…Research on travel planning has relied on structured surveys (Backhaus et al, 2022;Huh & Park, 2010;Litvin et al,2004;Mone & Crotts, 2003) or scenario-base experiments (Rahman et al, 2018) with a sample design delimited in nature and size to observe differences in trip planning time/horizon between individuals from different countries and between traveller-related or trip-related determinants. These studies also differ in how travel planning time/horizon is defined and operationalized.…”
Section: Trip-planning Behaviour Under Ordinary Circumstancesmentioning
confidence: 99%
See 3 more Smart Citations